Black & white : the rise and fall of Bobby Fischer - Voloj, Julian (Abrams Comicarts, 2023)
"A graphic novel biography following the life of Bobby Fischer, from chess wunderkind and national hero to his eventual spiral into madness and infamy."--Amazon.